Analysis of the Financial Inclusion Effect on the Stability of the Financial System in South East's Developing Countries - Awanti, Erni (Jurnal Ilmu Ekonomi Terapan, 2017)
This research aims to analyze the impact of financial inclusion on financial system stability and its determinants in Southeast Asian countries from 2007 to 2015. A multidimensional index of financial inclusion (IFI) was used to analyze the financial inclusion index and panel data regression with Fixed Effect Model (FEM) was used to analyze the impact between variables. The estimation using IFI shows that Malaysia has the highest financial inclusion index and estimation using FEM shows that the financial inclusion variable has a negative and not significant impact on financial system stability. Other variables which have a positive and significant impact on financial system stability are GDP per capita, private credit ratio, and liquidity asset ratio. Otherwise, the financial openness index has a negative and significant impact on financial system stability.